A qualitative study on the views of experts on the social impact of the high-priced orphan drug nusinersen - Sara Rosenberg; Björn Södergård; Jessica M. Rosenholm; Jussi-Pekka Rauha (Elsevier, 2023)
Background: Escalating medical costs due to the increasing occurrence of high-priced orphan drugs is a topic discussed in the media and specialist literature. However, there is no study investigating the social impact of such drugs through the views of experts. Objectives: The aim was to demonstrate the social impact of the orphan drug nusinersen based on the views of experts within the community. Methods: The study was conducted using two methods for data collection: a media analysis and qualitative semi-structured interviews. In the media analysis, expert comments on nusinersen were extracted from the Finnish media. Interviews were conducted with experts from the fields of pharmacy, medicine, politics/academia, law/economics, hospital management and patient organisations from different parts of Finland, who encountered nusinersen in their profession. Participants were recruited through purposive and snowball sampling. Interviews were audio-recorded, transcribed verbatim, and the overall data were analysed thematically. Results: Twenty-nine media references were collected, and 16 interviews conducted. Three main themes were identified: ethical aspects, financial aspects, and call for new strategies. Expert views were divided between the ethical and financial aspects of nusinersen. These existed alongside each other, showing that different attitudes and values compete with each other, and may be classified in different ways depending on the situation. However, the discussion quickly evolved into a call for new strategies in order to find solutions to issues concerning orphan drugs and the social impact created as a result. Conclusions: This study reveals the social impact of nusinersen thus far within the community and it appears somewhat different when seen from the perspectives of patients and decision-makers. Even though impact has been created, such as the establishment of a disease-specific patient organisation, other issues still require further research. Among these are the potential establishment of international collaboration forums for price negotiations with pharmaceutical companies.